Pengaruh Stabilitas Keuangan, Ketidakefektifitas Pengawasan, Auditor Switching, dan Tekanan Eksternal terhadap Kecurangan Laporan Keuangan: Studi Empiris pada Perusahaan Badan Usaha Milik Negara yang Terdaftar di BEI Tahun 2019–2023 - Raja Mayang Aysha; Hardi Hardi; Eka Hariyani (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
Financial statement fraud is the deliberate disclosure of a company's financial condition with material misstatements intended to deceive users of the financial statements for personal gain (Association of Certified Fraud Examiners (ACFE), 2020). This research aims to explore the impact of financial stability, ineffective monitoring, auditor switching, and external pressure on financial statement fraud. It focuses on BUMN companies listed on the Indonesia Stock Exchange (IDX) in 2019-2023. The sample selection in this study used a nonprobability sampling method. The number of sample companies was fixed, namely 24 companies. The data analysis method used was multiple linear regression. The results of the study indicate that financial stability, ineffective monitoring, and external pressure have a significant effect on financial statement fraud. Meanwhile, auditor switching has no significant effect on financial statement fraud.